Aksjologiczna wykładnia prawa - Kordela, Marzena (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
Both derivative and clarification conceptions of legal interpretation specify among basic types, linguistic, functional and systematic interpretations. This catalogue does not include axiological interpretation as a separate category. Nevertheless, in the derivative theory, values make up a fundamental (and in its initial version — even sole and unique) element of functional interpretation, whereas in the clarification theory in the same type of interpretation they are on a par with many other elements, such as e.g. type of political system or economic phenomena. In light of greater importance attached to values in the collection of interpretational arguments, primarily in the connection with constitutional interpretation, it seems justifiable to extract a type of axiological interpretation from functional interpretation. Then, its main task would be to define a set of values qualified as the axiological system of the legislator, to extract values that are legally binding (legal values), to take a stand about the degree of value objectivity (as recreated by the interpreter by means of rational interpretational methods, or created, at least to a certain degree, by him), and to construct a set of axiological rules of interpretation, accommodating value specificity, such as e.g. their immanent conflicting nature, gradable character, or the necessity of applying a balancing procedure in an eventuality of a collision occurring between them
Keywords: aksjologia; teoria prawa; wykładnia prawa